2007
DOI: 10.1175/jcli4031.1
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Changes in Cloud Cover and Cloud Types over Land from Surface Observations, 1971–96

Abstract: From a dataset of weather observations from land stations worldwide, about 5400 stations were selected as having long periods of record with cloud-type information; they cover all continents and many islands. About 185 million synoptic reports were analyzed for total cloud cover and the amounts of nine different cloud types, for the 26-yr period 1971-96. Monthly and seasonal averages were formed for day and night separately.Time series of total-cloud-cover anomalies for individual continents show a large decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
183
1
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(208 citation statements)
references
References 71 publications
21
183
1
3
Order By: Relevance
“…Comparison between TCA timeseries for the Australian region provided by Warren et al (2007) and our results, for the common period , reveals negative trends of similar magnitude. This similarity occurs despite the fact that two analysis are based on different number of stations (74 and 165 respectively) and Warren et al include neighboring Pacific Islands.…”
Section: Trend Analysissupporting
confidence: 69%
See 1 more Smart Citation
“…Comparison between TCA timeseries for the Australian region provided by Warren et al (2007) and our results, for the common period , reveals negative trends of similar magnitude. This similarity occurs despite the fact that two analysis are based on different number of stations (74 and 165 respectively) and Warren et al include neighboring Pacific Islands.…”
Section: Trend Analysissupporting
confidence: 69%
“…A comprehensive study of global trends in cloud amount was undertaken by Warren et al (2007). The study found a small negative trend in global average cloud cover over land for the period 1971 to 1996, which was compensated by a small positive trend over the ocean, resulting in almost no trend for global average cloud cover over the period considered.…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding global and temporal average cloud coverages resulting from long-term surface observations have been published by e.g. Warren et al (2007) and are given in Table 1. The measured cloud coverages already include a certain amount of overlap between the different cloud layers, which was not further specified by Warren et al (2007).…”
Section: Cloud Model Descriptionmentioning
confidence: 99%
“…Warren et al (2007) and are given in Table 1. The measured cloud coverages already include a certain amount of overlap between the different cloud layers, which was not further specified by Warren et al (2007). Average properties of Earth clouds, for instance the cloud top temperature and pressure as well as their optical depth have been derived by long-term satellitebased measurements within the International Satellite Cloud Climatology Project (ISCCP) for example.…”
Section: Cloud Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation